2001
DOI: 10.2169/internalmedicine.40.911
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Presenting with the Syndrome of Inappropriate Secretion of Antidiuretic Hormone after Simple Mastectomy.

Abstract: A 71-year-old womanshowed disorientation 7 days after simple mastectomy for right breast cancer. Computed tomography of the brain was normal. The level of serum sodium was very low (110 mEq//), while the urine sodium level was normal. The osmolality of urine was higher (342 mosmol/kg) than that of serum (220 mosmol/kg). These data suggested a syndrome of inappropriate secretion of antidiuretic hormone. A fluid restriction, infusion of hypertonic saline and administration of diuretics gradually increased the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Recently there have been reports of SIADH in patients undergoing minor surgeries, such as laparoscopic cholecystectomy, appendectomy, and cataract extraction under local anesthesia [2][3][4][5][6][7][8][9][10][11][12]. In terms of endoscopic treatment, no case of SIADH has been reported, although several reports have shown patients with hyponatremia after preparation for colonoscopy [17][18][19].…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently there have been reports of SIADH in patients undergoing minor surgeries, such as laparoscopic cholecystectomy, appendectomy, and cataract extraction under local anesthesia [2][3][4][5][6][7][8][9][10][11][12]. In terms of endoscopic treatment, no case of SIADH has been reported, although several reports have shown patients with hyponatremia after preparation for colonoscopy [17][18][19].…”
Section: Case Reportmentioning
confidence: 99%
“…Miller et al [27] reported findings of a large study of apparent idiopathic hyponatremia in an ambulatory geriatric population, which supports the hypothesis that aging is a risk factor for the development of SIADH-like hyponatremia in patients with no other apparent underlying etiology. Some authors have reported that elderly patients with a preoperative serum sodium concentration at the lower end of the normal range developed SIADH after relatively minor surgeries [3,8]. They believed it reasonable to recognize that their patients might be within a subset of elderly people at risk for developing SIADH without other risk factors, and that a relatively minor surgical procedure might have increased their patients' susceptibility to the syndrome.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…All these changes associated with aging would provide the inclination to hyponatremia. The paper by Hashida et al (6) in the present issue describes a case of 7 1-year-old womanshowing the syndrome of inappropriate secretion of antidiuretic hormone (SIADH) after mastectomyfor breast cancer.…”
mentioning
confidence: 99%